ANTONYMIC RELATIONS IN FRENCH PHYSICS TERMINOLOGY - Halyan , Oksana (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article addresses the topical issue of antonymy in a terminology system. The author reviews classifications of antonyms based on the semantic and structural criteria. A contrastive analysis of antonymic pairs as an opposition category is performed from the conceptual-semantic perspective. The basis of antonymic relations in a physics terminology system is the semantics of a hypernym term. It determines the extreme hyponym terms through which opposition is realized. It is shown that antonymic pairs in the lexicon of common usage and in a terminology system are not identical. The author posits that this is due to antonymic pairs acquiring new semantic elements while preserving key semantic features present in commonly used words. Antonymic terms in physics can enter into synonymic relations and form synonym sets whose functionality depends on the context of scientific text. Antonyms among physics terms have been divided into contrary (gradual), complementary, and vectorial based by the semantic criterion. The article describes their semantic characteristics and peculiarities of functioning in texts. In particular, contrary antonymic pairs denote two opposite kinds of concepts, between which there are one or more intermediate terms indicating the increase or decrease of a conceptual feature. Complementary antonymy is characterized by the fact that words that are opposed through hyponym terms complement of a single hypernym term and do not contain any intermediate lexical elements. In this kind of antonymy, it is necessary to clearly identify both elements of opposition to avoid ambiguity in the opposition of physical terms. Vector antonymy consist in the opposite of different actions, motions, signs and is quite common in physics terminology.______________References• Balli, Sh. Obshchaya lingvistika i voprosy frantsuzskogo yazyka (Moskva, Inostrannaya literatura, 1955), 416.• Gavrilova, N. V «Delovaya terminologiya mezhdunarodnoy ekonomiki vo frantsuzskom, angliyskom i russkom yazykakh v tezaurusnom aspekte.» Avtoref. dis. kand. filol. nauk, Ekaterinburg, 2009.• Danilenko, V. P. «Leksiko-semanticheskie i gramaticheskie osobennosti slov-terminov.» Issledovaniya po russkoy terminologii (Moskva, Nauka, 1971): 7–67.• Zhernovej, Je. G. «Religijna terminologija suchasnoi' francuz'koi' movy: geneza, semantyka, funkcionuvannja.» Avtoref. dys. kand. filol. nauk, Kyi'v, 2003.• Lopatnikova, N. N. Leksikologiya sovremennogo frantsuzskogo yazyka (Moskva, Vysshaya shkola, 1971), 150.• Nikolaeva, M. A. «Antonimiya prilagatel'nykh v sovremennom frantsuzskom yazyke.» Avtoref. dis. kand. filol. nauk, Moskva, 1976.• Novikov, L. A. Antonimiya v russkom yazyke (Moskva, Izd-vo Mosk. un-ta, 1973), 289.• Novikov, L. A. Semantika russkogo yazyka : uchebnoe posobie (Moskva, Vysshaya shkola, 1982), 272.• Shiganova, G. A., Surovtseva, S. I. «Antonimiya predlogov kak yavlenie sistemy (na materiale russkogo i frantsuzskogo yazykov).» Vestnik Chelyabinskogo gosudarstvennogo pedagogicheskogo universiteta 11 (2012): 328–335.• Giermak-Zielinska Teresa. «Les adjectifs antonymes – statut logique et interprétation sémantique.» Langages 23e année89 (1988): 109–• Le Garrec, B., Di-Nicola, J. M., Beau, V., Julien, X. «Metrologie des faisceaux et de la tache focale de la LIL.» Phys. IV France 138 (2006): 297–307.• Pascal Amsili. Antonymie, access http://www.semantique-gdr.net/dico/index.php/Antonymie